Natural gas combustion in diesel engine - Lopatin, O P (IOP conference series. Earth and environmental science, 2020)
The article is devoted to the use of natural gas as an alternative fuel for diesel engines. When operating the diesel engine on natural gas with an additional portion of the diesel fuel are distinctive features of the processes of mixture formation and combustion, there is heterogeneity of the combustible mixture in the cylinder, more fuel evaporation and other aspects of the processes of formation of the fuel-air mixture and its combustion. Consequently, the use of alternative fuels with different chemical composition leads to distinctive indicators of the combustion process. Therefore, for the scientific representation of the real picture of the combustion process in a diesel engine running on natural gas, it is necessary to conduct an indication of its working process and a detailed description of the combustion process.